2017
DOI: 10.4236/ss.2017.812058
|View full text |Cite
|
Sign up to set email alerts
|

Urological Complications of Gynecological and Obstetric Interventions: Management at the Ignace Deen National Hospital—University Hospital of Conakry (Guinea)

Abstract: Introduction: pelvic abdominal surgery may be associated with urological complications requiring reoperation. The aim of this study was to evaluate the urological surgical complications of gynecological and obstetric procedures conducted at the Ignace Deen University Hospital of Conakry in Guinea. Methodology: This was a retrospective, cross-sectional, descriptive study of ten years, from 1 January 2006 to 21 December 2015. Results: Of 14,500 patients hospitalized in the maternity ward during the study period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
1
2
2
Order By: Relevance
“…Renal insufficiency was noted in ten (71.4%) patients. This Open Journal of Obstetrics and Gynecology result is similar to Diallo in Guinea, who found elevated creatinine in 72.2% of patients with iatrogenic lesions of the ureter [9]. In nine out of fourteen cases bilateral ligation of the ureters was found.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Renal insufficiency was noted in ten (71.4%) patients. This Open Journal of Obstetrics and Gynecology result is similar to Diallo in Guinea, who found elevated creatinine in 72.2% of patients with iatrogenic lesions of the ureter [9]. In nine out of fourteen cases bilateral ligation of the ureters was found.…”
Section: Discussionsupporting
confidence: 72%
“…The patients in our study were predominantly young, with an average age of 32.9 years (range 20 -60 years 74.36% of iatrogenic lesions of the ureters were attributable to Caesarian section [9]. Caesarian section is the most common surgical procedure resulting in iatrogenic lesions of the ureters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This average delay is lower than that obtained by Diallo, A. B. et al (5 months) [7] but higher than that obtained by Bouya, P. A. (15 days) [1].…”
Section: Discussioncontrasting
confidence: 61%
“…Our results were comparable to those of Saad B et al [3] in Morocco who found a frequency of 63.6%. But superior to those of Diallo FB et al [5] in Guinea who reported 40.55% of complications. This high frequency could be explained by the introduction of free caesarean sections, the existence of residents in the obstetrics gynecology departments in the University Hospital of Conakry and the multitude of clandestine surgeries in our capital.…”
Section: Discussioncontrasting
confidence: 55%